2021
DOI: 10.3390/ijerph18084231
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Consumption during the COVID-19 Pandemic—Small Change in Total Consumption, but Increase in Proportion of Heavy Drinkers

Abstract: Little is known about possible changes in alcohol consumption distribution during the COVID-19 pandemic. We estimated how individual changes in alcohol consumption during the pandemic translated into changes in: (i) mean consumption; (ii) dispersion of consumption distribution; and (iii) prevalence of heavy drinkers. We employed data from two independent web-surveys of Norwegian adults collected between April and July 2020 and limited to those reporting past year alcohol consumption (N1 = 15,267, N2 = 1195). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 33 publications
7
41
1
2
Order By: Relevance
“…In South Korea, a preliminary survey of 1,017 participants showed that a majority (61.9%) of pre-pandemic heavy/frequent drinkers (≥4 times a week) showed increased alcohol consumption during the outbreak, while a majority of former moderate (64.7%), light (70.9%), or non-drinkers (55.8%) (≤3 times a week) showed decreased alcohol consumption ( 20 ). Similarly, an online survey conducted by the Norwegian Directorate of Health in June–July 2020 with 1,328 respondents (aged 18 years and above) selected randomly from a national web panel reported that the upper 5–10% of heavy drinkers (≥~8.8 drinks a week) during the COVID pandemic increased their alcohol consumption, thereby increasing the prevalence of heavy drinkers ( 43 ). Additionally, a European online survey (40,064 participants aged 18 years and older) in 21 European countries showed an increase of harmful alcohol consumption (AUDIT-C score ≥8), but not in low harmful alcohol consumption (AUDIT-C score ≤7) ( 44 ).…”
Section: Problematic Alcohol Consumption During the Covid-19 Pandemicmentioning
confidence: 99%
“…In South Korea, a preliminary survey of 1,017 participants showed that a majority (61.9%) of pre-pandemic heavy/frequent drinkers (≥4 times a week) showed increased alcohol consumption during the outbreak, while a majority of former moderate (64.7%), light (70.9%), or non-drinkers (55.8%) (≤3 times a week) showed decreased alcohol consumption ( 20 ). Similarly, an online survey conducted by the Norwegian Directorate of Health in June–July 2020 with 1,328 respondents (aged 18 years and above) selected randomly from a national web panel reported that the upper 5–10% of heavy drinkers (≥~8.8 drinks a week) during the COVID pandemic increased their alcohol consumption, thereby increasing the prevalence of heavy drinkers ( 43 ). Additionally, a European online survey (40,064 participants aged 18 years and older) in 21 European countries showed an increase of harmful alcohol consumption (AUDIT-C score ≥8), but not in low harmful alcohol consumption (AUDIT-C score ≤7) ( 44 ).…”
Section: Problematic Alcohol Consumption During the Covid-19 Pandemicmentioning
confidence: 99%
“…Implicitly, this leads us to the expectation that when the total consumption remains stable, so does the prevalence of heavy drinking and related harm rates. However, this relationship seems not necessarily to be the case always, and a recent study from Norway [ 9 ] found increased rates of heavy drinking despite a small decrease in total consumption during the first months of the COVID-19 pandemic. In this study, we explore whether this could also apply to other European countries.…”
Section: Introductionmentioning
confidence: 99%
“…These findings may suggest two preliminary conclusions; (i) that those drinking at heavy levels changed their consumption differently from other drinkers, and (ii) that despite a preponderance of people reporting reduced drinking, the overall consumption levels—in these survey samples—did not necessarily decrease. For example, the above-mentioned study from Norway [ 9 ] found that during the first phase of the COVID-19 pandemic (i.e., March to May 2020), the estimated overall change in alcohol consumption was small. However, among drinkers in the upper 10% of initial consumption (i.e., in the upper 10% of drinkers before or at the start of the pandemic situation), there was an increase in consumption, pushing a number of these drinkers above the high-risk threshold; hence, the estimated prevalence of high-risk drinkers seemed to increase during the first phase of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Another study could show that alcohol consumption of heavy drinkers significantly increased. 7 Alcohol consumption is the main trigger of acuteon-chronic liver failure (ACLF), 8 which is a frequent syndrome in patients with underlying liver cirrhosis and is characterised by acute decompensation of cirrhosis, organ failure(s) and high short-term mortality. 9 We retrospectively analysed the prevalence and outcome of patients with ACLF precipitated by severe alcoholic hepatitis in a non-COVID-19 intensive care unit (ICU) of the University Liver Center in Frankfurt am Main (Hesse, Germany) during the SARS-CoV-2 pandemic in 2020 in comparison with equivalent time periods between 2017 and 2019.…”
mentioning
confidence: 99%